ECONOMIC AND LEGAL CHARACTERISTICS OF PUBLIC AUTHORITIES OF UKRAINE - Oleg Dubynskyy; Dmytro Baranenko; Vitalii Porkhun (Baltic Journal of Economic Studies)
The study of public authority is relevant for many reasons. Firstly, public authority is a complex and multifaceted phenomenon that is constantly evolving. Secondly, public authorities have a significant impact on society, and it is important to understand how they function. Thirdly, the study of public authorities can help to develop effective methods of governing society. The research of public authority is conducted in various fields of knowledge, such as public administration, political science, law, economics, sociology, and philosophy. The interdisciplinary investigation of public authority is also important, as it allows for a deeper understanding of this phenomenon. The current stage of development of the Ukrainian state is determined by the need to build a public administration system that will ensure effective interaction between public authorities (state and local governments) and civil society. Public administration is a system of governance in which state and local authorities, various organisational and legal forms and citizens directly involved in the process of social development of the state interact. The key objective of the formation and functioning of the public administration system is to develop and implement socio-economic policies aimed at improving the living standards of the population. The success of its implementation depends not only on the functioning of various state institutions, but also on the extent to which society accepts this policy, shares its goals, mechanisms, principles of its implementation, and trusts it. The purpose of the article is to study and analyse the concept and features of public authority in the current conditions of development of public relations, and to establish the link and interdependence between the conceptual foundations, objectives, subjective dimension of decentralisation of public authority in Ukraine and its economic, political, legal and administrative consequences. The methodological basis of the article is a system of general scientific and special methods of scientific knowledge. These methods together constitute an integral system, which is manifested in the quality of the research approach, both at the empirical and theoretical levels of this scientific work. It is noted that the role of local self-government bodies during wartime should not be underestimated; they remain an important mechanism for ensuring the effective functioning of public authorities and the defence capability of the State. This was clearly evidenced by the actions of local self-government bodies in the first days of the large-scale invasion of Ukraine by the Russian Federation. In the authors' opinion, the experience gained by Ukraine during the war demonstrates the undeniable advantage of self-organisation of the population over centralised governance. The central government will not be able to take over the functions of local governments and perform them as effectively. Even before the war, the level of trust in local authorities among citizens was one of the highest compared to other institutions. Recently, as citizens have been interacting more and more with local authorities, as they are closest to them, this attitude has only strengthened. Therefore, the termination of the powers of local self-government bodies by the state authorities during the war is an unconstitutional action that threatens the national security of the country. Suspension or restriction of their powers is possible only in extraordinary cases, when there is a direct threat to the life and safety of citizens in the territory of hostilities or occupation. In all other cases, this is possible only in accordance with a procedure that requires a reasoned court decision. However, the political and legal reality caused by the full-scale invasion of Ukraine by the Russian Federation on February 24, 2022, showed a low level of drafting and lawmaking, their abstract and declarative nature, internal contradictions and outright neglect of the interests of the territorial community and its members, which directly and negatively affected the procedure for exercising the powers of self-government bodies, including the protection of human rights and freedoms within the local society.